1992
DOI: 10.1017/s027226310001113x
|View full text |Cite
|
Sign up to set email alerts
|

Grammaticalization Processes in the Area of Temporal and Modal Relations

Abstract: This study investigates some instances of linguistic development in the acquisition of a second language that might be subsumed under the issue of grammaticalization. First, the notion of grammaticalization is discussed with reference to the current linguistic debate and its applicability to the domain of language acquisition is evaluated. Then, some cases are examined drawing on data on the acquisition of Italian collected during several years at the University of Pavia. With respect to temporality and modali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
6

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 18 publications
1
46
0
6
Order By: Relevance
“…The latter form mostly expresses a temporal/aspectual meaning of pastness and perfectivity. In all the learners observed (Giacalone Ramat 1992Ramat , 2003, the functional opposition between the perfective aspect expressed by the passato prossimo and the imperfective aspect represented by the imperfect was acquired later than the present-passato prossimo opposition. Even later, the means were acquired for the morphological expression of the future.…”
Section: Some Results From the Acquisition Of Tense And Aspect In L2 mentioning
confidence: 94%
“…The latter form mostly expresses a temporal/aspectual meaning of pastness and perfectivity. In all the learners observed (Giacalone Ramat 1992Ramat , 2003, the functional opposition between the perfective aspect expressed by the passato prossimo and the imperfective aspect represented by the imperfect was acquired later than the present-passato prossimo opposition. Even later, the means were acquired for the morphological expression of the future.…”
Section: Some Results From the Acquisition Of Tense And Aspect In L2 mentioning
confidence: 94%
“…Although the relatively simple form of English modals can generally be learnt easily, there is evidence that mastering the complexity of modal semantics and pragmatic inferences willnecessitateaninvestmentofconsiderablymoreeffortandtimeonthepart of the learner (Dittmar and Terborg 1991;Giacalone Ramat 1992). In the Pavia Project Giacalone Ramat and her colleagues longitudinally studied the acquisition of L2 Italian by learners coming from different L1 backgrounds (Chinese, Tigrinya, Persian, German andEnglish).Itwasobservedthatatearly stages of acquisition only deontic modality was used in grammaticalised, inflected verb forms, whereas a limited range of epistemic meaning was achieved by the use of epistemic adverbs (in Italian forse and magari, meaning 'perhaps' or 'maybe') and some basic formulaic expressions with modal verbs, such as non (lo) so,me aning'Idon'tknow'.…”
Section: L2 Acquisition Of English Modal Verbsmentioning
confidence: 99%
“…On the other hand, studies on conceptual transfer have been predominantly concerned with productive use of language, and likewise, studies in L2 acquisition of modality have so far mostly been interested in the production of modal verbs. Important longitudinal studies that investigated the development from deontic/dynamic to epistemic use of modal auxiliaries in both L1 and L2 production (e. g. Dittmar and Terborg 1991;Giacalone Ramat 1992;Stephany 1986) were not matched by research concerned with comprehension issues. Therefore, studies focusing on L2 comprehension of epistemic modality are clearly needed.…”
Section: Cross-linguistic Influencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important series of studies known as the Pavia Project focused on the L2 acquisition of Italian, a Romance language with a passato prossimo-imperfetto distinction corresponding to the perfective-imperfective, by adult learners of various L1 backgrounds (e.g., Giacalone Ramat, 1992Giacalone Ramat & Banfi, 1990). It was observed that verbal morphology developed late, with a progressive move from a reliance on lexical means to the acquisition of the target language morphological endings.…”
Section: Select Previous Studiesmentioning
confidence: 99%